“On Earth as it is in Heaven”: Prophecy and Class in the Works of Ibn Daud - Hamilton, Michelle (Anales del Seminario de Historia de la Filosofía, 2023)
Abraham ibn Daud’s Exalted Faith adapts to rabbinic thought and Jewish tradition the Andalusi Aristotelian model that was the framework for understanding God, man, and man’s purpose in the universe. Ibn Daud defines Jewish belief for the perplexed scholar, arguably providing a genealogy and epistemological justification for the scholarly class—based on acquisition of knowledge of the (Aristotelian) universe and culminating in achieving prophethood. The Aristotelian universe presented in the Exalted Faith offers a version of the elitism Stroumsa argues if at the heart of this Jewish and Muslim scholarly class, one based in Arabic Aristotelian thought. The prevalence of Aristotelian-Farabian (Platonic) philosophy, which held as a central tenet the individual’s ability to know God by developing his intellect through speculation, seemingly offered a religious/societal model in which Jewish traditions and commandments were no longer relevant. Ibn Daud adapts this theory to reassert the necessity for Jewish traditions and to privilege Jewish scholars. to express a vision of individual and social identity for Sephardi scholars in the Diaspora.